1976
DOI: 10.1152/jn.1976.39.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory actions of human stretch reflex

Abstract: 1. The stretch reflex in the elbow flexor musculature was studied in 23 human subjects. The subjects were required to establish an initial force equivalent to 10% maximum at a prescribed initial length; mechanical disturbances delivered at random times increased load force to 15% or reduced it to 5%. We measured arm force, displacement, and EMG (usually biceps); acceleration was calculated from displacement, and average responses from sets of 10 like trials. 2. Modification of the stretch reflex was studied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
212
4
4

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(241 citation statements)
references
References 33 publications
21
212
4
4
Order By: Relevance
“…The reaction time for each subject was taken to be the minimum latency of EMG onset following each perturbation. Since the responses were simple and independent of the direction of motor movement, they were likely to be pre-programmed, triggered reactions (Crago et al 1976). …”
Section: Protocolmentioning
confidence: 99%
“…The reaction time for each subject was taken to be the minimum latency of EMG onset following each perturbation. Since the responses were simple and independent of the direction of motor movement, they were likely to be pre-programmed, triggered reactions (Crago et al 1976). …”
Section: Protocolmentioning
confidence: 99%
“…An additional potential source of information for the corrective system might be proprioceptive input from the limb (see dotted arrow). It has been suggested that proprioceptive information can modify EMG responses with a delay of only 70 msec (Crago et al, 1976).…”
Section: Correcting Erroneous Responsesmentioning
confidence: 99%
“…However, there remains controversy regarding the specificity of its modulation and the pathways that regulate this modulation. In particular, it has been suggested that the apparent facilitation of response amplitude when subjects are preparing to oppose a perturbation arises through an increase in the level of activation of the target muscle prior to the stretch (Capaday et al 1994), or that it represents the initial components of a triggered (Crago et al 1976) or voluntary (Rothwell et al 1980;Hallett et al 1981) reaction in the M2 time period.…”
Section: Introductionmentioning
confidence: 99%